An evaluation of IEEE 802.11 mac layer handoff process in CAPWAP centralized WLAN - Balfaqih, Mohammed; Nordin, Rosdiadee; Balfaqih, Zain; Haseeb, Shariq; Hassan Abdalla Hashim, Aisha (Little Lion Scientific Islamabad Pakistan, 2015)
The growing demand to provide secure wireless connectivity, especially in hot spot areas such as conference halls and events, motivated the development of Control and Provisioning of Wireless Access Point (CAPWAP) centralized Wireless Local Area Network (WLAN). The centralized WLAN utilizes an Access Controller (AC) to simplify configuration, management, and control of Wireless Termination Points (WTPs) in large scale deployment of a wireless network. In order for the clients to associate and reassociate to WTPs, scanning and authentication phases are performed. The contributed latency during scanning and authentication phases, in the MAC layer handoff process, makes it difficult to support realtime applications that are sensitive to network latencies. This work simulates the effect of using different scanning and authentication methods in CAPWAP centralized WLAN during MAC layer handoff process. This can be considered as a significant contribution since no prior work has been done, to our knowledge, to simulate the handoff latency components in centralized networks. This work also studies the effect of varied propagation environments including isolation, and indoor and outdoor environments on handoff process. Moreover, the effects of employed WTP type and the client movement speed on the handoff process latency have been analyzed. Keywords: Handoff, CAPWAP, Scanning, Authentication, Centralized Network.